(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article explores the psychology of teenager in the novel by the Polish writer Joanna Jagello «Coffee with Cardamom» through their actions, behavior, moral tests. It focuses on revealing the inner world of the main character - Halina Barskaya, searching for a girl of her own self-identity, self-realization; the means of creating characters of teenager in the novel. The detective nature of the novel, socially-psychological and symbolic-philosophical subtext are revealed.